Spent Pleurotus ostreatus substrate has potential for controlling the plant-parasitic nematode, Radopholus similis in bananas - Tazuba, Anthony Fredrick; Ocimati, Walter; Ogwal, Geofrey; Nyangwire, Betty; Onyilo, Francis; Blomme, Guy (MDPI, 2025)
Spent mushroom substrate (SMS), a waste product from mushroom cultivation, in addition to being rich in essential nutrients for crop growth, contains actively growing mushroom mycelia and metabolites that suppress some plant pathogens and pests. SMS thus has potential for fostering the suppressiveness of soil-borne pathogens of farms. This study determined the potential of using the spent Pleurotus ostreatus substrate (SPoS) to suppress the plant-parasitic nematode Radopholus similis in bananas. R. similis is the most economically important nematode in bananas worldwide. The effect of SPoS on R. similis was assessed through two in vivo (potted plants) experiments between May 2023 and June 2024. Five-month-old East African highland banana (genome AAA) plantlets that are highly susceptible to R. similis were used. In the first experiment, the plantlets were established in 3 L pots containing (i) pre-sterilized soil, (ii) pre-sterilized soil inoculated with nematodes, (iii) pre-sterilized soil mixed with 30% (v/v) SPoS, (iv) pre-sterilized soil mixed with 30% (v/v) SPoS followed by nematode inoculation, (v) SPoS without soil, and (vi) SPoS without soil inoculated with nematodes. The SPoS was already decomposed; thus, it may or may not have contained active mycelia. The nematodes were introduced two weeks after the SPoS application. In the second experiment, SPoS was introduced two weeks after nematode inoculation. The SPoS treatments without soil were not evaluated in the second experiment. Both experiments were monitored over a three-month period. Each screenhouse treatment contained four plants and was replicated thrice. In the first experiment, data were collected on changes in soil nutrient content, below- and aboveground biomass, root deaths, root necrosis due to nematode damage, and R. similis population in root tissues and soil. In the second experiment, data were collected on root deaths and the number of nematodes in root tissues and the soil. The SPoS improved crop biomass yield, reduced root damage, and colonization by R. similis. The potential of SPoS to improve the management of R. similis and banana production under field conditions needs to be determined.